Influence of Spanish on the English language since 1801 : a lexical investigation - Schultz, Julia (University lecturer) (Cambridge Scholars Publishing, 2018)
While there are numerous investigations of the impact English has exerted on Spanish, the reverse language contact scenario has received comparatively little attention. This book sheds light on the Spanish influence on the English vocabulary since 1801, offering the first systematic analysis of the multitude of words which have been taken over from Spanish and its national varieties over the past few centuries. The results provided by this study rely on the evaluation of a comprehensive lexicographical sample of 1355 Spanish borrowings collected from the Oxford English Dictionary Online. The f.